Farmers’ indigenous knowledge on local herbaceous forages in the Northeastern highlands of Ethiopia - Hussen Ebrahim; Yeshambel Mekuriaw; Bimrew Asmare; Netsanet Beyero; Fentahun Meheret Zeleke; Shewaye Hailecherkos; Endalew Mekonen; Zerihun Nigussie; Wubetie Adnew (PLoS ONE, 2026)
Natural pasture (NP) occupies the top place in livestock feed, particularly in frost-affected highland areas of Ethiopia. Despite numerous studies reporting the huge contribution of local herbaceous forages (LHF) in livestock production, the implementation of those results was not fruitful, attributable to overlooking farmers’ knowledge and experience. Therefore, the study was carried out to scrutinize the indigenous knowledge on LHF in the NP of the northeastern Highlands of Ethiopia. In the present study, we use 323 smallholder farmers (SHF) selected using systematic random sampling from two purposively selected Districts (Mekidela and Tenta) and eight Kebeles employing a multistage sampling procedure. The study analyzed the primary data and highlighted the relevance of SHF’s deep-rooted indigenous knowledge to improving NP and LHF. The findings confirmed that livestock production is mainly dependent on NP in the study area. However, farmers perceived that the NP has been declining with time at an alarming rate, mainly due to forestland (index ( I) = 0.456), cropland ( I = 0.338), and resettlement ( I = 0.139) expansion. The study elucidated that land shortage ( I = 0.172), lack of awareness ( I = 0.17), and eucalyptus expansion ( I = 0.151) were the first, second, and third ranked challenges of utilizing LHF. Farmers reduced animal numbers ( I = 0.234) and practiced zero grazing ( I = 0.34) to improve the LHF in the NP during the dry and wet seasons, respectively. Moreover, further investigations are required to elucidate more merits of LHF species, determine their species diversity, and evaluate their morphological characters.